FAKTOR PENENTU ALIH FUNGSI LAHAN SAWAH DI TINGKAT RUMAH TANGGA PETANI DAN WILAYAH DI PROVINSI BALI - Suharyanto ,; Ketut Mahaputra; Nyoman Ngurah Arya; Jemmy Rinaldi (Balai Besar Pengkajian dan Pengembangan Teknologi Pertanian, 2016)
ABSTRACTDeterminants of Paddy Land Conversion in Household Level and Regional in Bali Province. Land conversion of paddy area for other purposes has become a serious threat to the sustainability of food security and existence of Subak institutional in Bali. The intensity of land conversion is still difficult to be controlled, and most of the wetland conversions are actually at the high-productivity categories. The objective of this research was to identify factors causing rice land conversion at the regional and farmer level. The research was conducted in March-November 2015. In this study, primary data was enriched with secondary data. The primary data was collected through individual interviews with 90 farmers in three rice center production areas which were Tabanan regency, Badung regency and Buleleng regency. Moreover, the secondary data was taken from Statistics Indonesia using the data period of 1993-2013. Multiple linear regressions with Ordinary Least Square method (OLS) was used to analyse the data at the regional level whereas logistic regression was employed to examine the household level data. The results showed that the growth rate of non-agricultural Gross Domestic Product (GDP), rice production, population, hotels and other accommodations and Farmers Exchange Rate had a significant affect to the land conversion at the regional level. Local regulation related legislation at the provincial level did not affect the growth rate of land conversion. Meanwhile, the probability of farmers to sell or convert their lowland rice fields was affected by the tax value of the land, the productivity of paddy rice, the selling value of the land, and the proportion of paddy farm income to total household income. In addition, the probability of farmers to sell their farms was also greater if the condition of damaged irrigation and paddy location was close to the road.Keywords: land conversion, paddy field, regional, household ABSTRAK Alih fungsi lahan sawah untuk kepenggunaan lainnya menjadi ancaman serius terhadap keberlanjuan ketahanan pangan dan kelembagaan Subak di Bali. Intensitas alih fungsi lahan masih sulit untuk dikendalikan, dan kebanyakan lahan sawah yang beralihfungsi justru memiliki produktivitas tinggi. Penelitian ini bertujuan untuk mengidentifikasi faktor-faktor penyebab alih fungsi lahan sawah di tingkat wilayah dan rumah tangga petani. Penelitian dilaksanakan pada Maret-November 2015. Data yang digunakan adalah data primer diperkaya dengan data sekunder. Data primer dikumpulkan melalui wawancara terhadap 90 petani responden di tiga sentra produksi padi sawah yaitu Kabupaten Tabanan, Badung dan Buleleng. Sedangkan data sekunder memanfaatkan data BPS periode 1999-2013. Analisis data di tingkat wilayah menggunakan regresi linier berganda dengan metode Ordinary Least Square (OLS) sedangkan di tingkat rumah tangga menggunakan regresi logistik. Hasil penelitian menunjukkan bahwa laju pertumbuhan Produk Domestik Regional Bruto (PDRB) non pertanian, produksi padi, penduduk, hotel dan akomodasi lainnya dan Nilai Tukar Petani (NTP) memberikan pengaruh nyata terhadap laju konversi lahan sawah. Adanya peraturan daerah terkait Rencana Tata Ruang Wilayah (RTRW) juga tidak berpengaruh terhadap laju alih fungsi lahan sawah. Sedangkan peluang petani untuk menjual atau mengkonversi lahan sawahnya dipengaruhi oleh nilai pajak lahan, produktivitas padi, nilai jual lahan, dan proporsi pendapatan padi terhatap total pendapatan rumahtangga. Peluang petani untuk menjual lahan sawahnya juga lebih tinggi pada lahan dengan kondisi irigasi rusak dan dekat dengan jalan.Kata kunci: Alih fungsi, lahan sawah, wilayah, rumah tangga